Peptide extracted from quinoa by pepsin and alcalase enzymes hydrolysis: Evaluation of the antioxidant activity. Issue 10 (25th July 2020) - Mahdavi Yekta, Mina; Nouri, Leila; Azizi, Mohammad Hossein; Karimi Dehkordi, Maryam; Mohammadi, Milad; Jabbari, Maryam; Rezaei, Mohammad; Mousavi Khaneghah, Amin
Abstract: Defatted quinoa flour, as the extracted protein, was hydrolyzed with pepsin and alcalase enzymes. Twelve pretreatments (T1–12 ) were prepared with different temperatures, periods of time, and the ratio of enzyme to substrate to determine the optimum hydrolysis condition and evaluate their ability to inhibit ABTS free radicals. The increase in temperature, enzyme activity levels, and time caused a significant increase in the degree of hydrolysis (DH) while T12 with enzyme ratio 90 AU/kg and temperature of 55°C for 210 min displayed the highest DH. The highest ability to neutralize ABTS radicals (21.35% and 21.67%) were assigned to T7 (enzyme/substrate ratio 60, the temperature of 50°C) and T11 (enzyme/substrate ratio 90, the temperature of 50°C) for 150 min, respectively. The quinoa proteins as a potential source of antioxidant peptides could be applied as a useful food ingredient in the food industry. Practical applications: The quinoa protein‏has nutritional values and high quality, as well as containing high amounts of lysine, methionine, and cysteine amino acids as well as some antioxidant compounds such as flavonoids with high antioxidant activity. Therefore, they could be applied as a useful food ingredient in the food industry. However, the future investigations in incorporating quinoa biopeptides in different food matrices focusing on lipid oxidation and food stability and quality are required.